A Study on the Happiness of Elderly Individuals Who Remain Employed - Aloo, Pelipus; Pello, Shela Christine; Mage, Mernon Yerlinda Carlista; Damayanti, Yeni (Journal of Health and Behavioral Science, 2025)
Living happily in old age is the dream of every elderly person. Happiness is a positive psychological state in which an individual experiences positive emotions such as life satisfaction and positive feelings. This research aims to describe the happiness of the elderly who are still working in Kupang City. It uses a qualitative phenomenological approach with five elderly participants selected through purposive sampling. Five main themes were identified: full engagement, building positive relationships, meaning in life, optimism, and resilience. Data analysis involved data reduction, data presentation, and verification as research results. The findings revealed that the elderly could achieve desired life happiness, including having sufficient income, being independent and persistent, finding life meaning, spending time with family, having optimism for the future, and being able to rise from failure, despite psychological and physical changes in old age.